Money demand in Europe: Evidence from the past - Elke Hahn; Christian Müller (Deutsches Institut für Wirtschaftsforschung (DIW), 2000)
The conditions under which European monetary policy is likely to be conducted are investigated by means of multi-variate time series modelling using aggregated data of all eleven European Monetary Union member states. A cointegration analysis identifies two stable long-run relationships, one of which can be interpreted as a money demand function and a second one as a long term real interest rate (Fisher parity). Particular emphasis is given both to the data sources and their aggregation, by providing a transparent account of our calculation procedure, which is not yet common in the existing literature. – – Die Bedingungen, die der europäische Geldpolitik zugrunde liegen dürften, werden anhand einer multivariaten Zeitreihenanalyse unter Verwendung der Daten aller elf an der Europäischen Währungsunion teilnehmenden Länder untersucht. Im Rahmen einer Kointegrationsanalyse eines Systems von fünf Variablen konnten zwei stabile Langfristbeziehungen identifiziert werden, von denen die eine als Geldnachfragefunktion interpretiert werden kann, während die andere dem langfristigen Realzins entspricht (Fisher-Parität). Ein spezielles Augenmerk wurde auf eine möglichst transparente Darstellung der Datenquellen als auch der Aggregationsmethoden gelegt, was in der gegenwärtigen Literatur noch nicht als Standard angesehen werden kann.
Keywords: E41; E52; C32; 330; Geldnachfrage; Kointegrationsanalyse; Europäische Währungsunion; money demand; cointegration analysis; European Monetary Union; Geldnachfrage; Aggregation; Europäische Wirtschafts- und Währungsunion; Kointegration; Schätzung; EU-Staaten